First mature male record of Bathyraja schroederi Elasmobranchii, Arhynchobatidae) from the South Atlantic, with descriptions of its clasper and skeletal characters - Stehmann, Matthias F.w.; Pompert, Joost H.w. (Zootaxa, 2014)
The first mature male of Bathyraja schroederi (Krefft, 1968) is reported based on a single specimen caught by longline in nearly 2000 m depth at 53°S, 57°W in the Western South Atlantic. This is only the third record after the original description of this very rare deepwater skate that is mainly found in the southwestern Atlantic and with records off southern Chile. The hitherto unknown clasper and skeletal characters of this mature male are described here and compared with the original series of seven specimens. The mature male differs in some morphometrics and meristics from the exclusively female type specimens and shows in its clasper the peculiarity of large dorsal and ventral pseudosiphons.